ASSESSMENT OF THE IMPACT OF INSTITUTIONAL TRANSFORMATIONS ON THE QUALITY OF THE FINANCIAL STABILITY SYSTEM OF CREDIT INSTITUTIONS IN UKRAINE - Хуторна, Мирослава (Socio-economic relations in the digital society, 2019)
Investigating the credit institutions’ financial stability ensuring system we distinguish such features of its quality: its stability, efficiency, functional continuity, rationality of interconnections between elements. At the same time, this subject (quality of the enumerated system) was researched in the context of institutional transformations, which impetus was the global fi nancial crisis 2008. In this paper we revealed the content of the institutional changes that took place in the organization of interaction between the subjects of the credit institutions’ fi nancial stability ensuring system in Ukraine. A comparative analysis for identifying the level of development of the credit institutions’ financial stability ensuring system at the global, supranational (European Union) and national levels allowed us to conclude that by 2011 in Ukraine existed a set of institutions with weakly adjusted communication, instead of efficient system. That is why until 2011 in Ukraine responsible authorities for the credit institutions’ stability almost independently developed the methodology of ensuring the financial stability of individual subsegments of the credit segment of the financial sector what is fully opposite tothe systemic approach used in the European Union. It is substantiated that special attention should be paid to the reform of the institute of financial stability of non-bank credit institutions. In our opinion, one of the obligatory steps should be consolidation the function of regulation and supervision on the activities of all types of credit institutions in one institution. At the current stage of development of the domestic institute of regulation and supervision, we consider it expedient to grant such powers to the National Bank of Ukraine. First of all, this will increase the eff ectiveness of the policy of the National Bank to ensure credit institutions’ financial stability, which eff ectiveness currently limited, if the risks are outside the perimeter of the banking sector. In the future, we consider it more expedient to create a separate supervisory institution. Also, the perspective institutional and functional scheme of interaction between the authorities-providers financial stability of the credit segment of the financial sector and the preconditions for its successful practical implementation are substantiated.
Keywords: financial stability; credit institutions; institutional provision of financial stability; the quality of the credit institutions’ financial stability ensuring system